Parental smoking practices and children's health risk from exposure to smoking - Elsaieh, Fatma Masoud; Shohaimi, Shamarina; Mohd Nadzir, Mohd Noor Hisham; Mohd Puad, Mohd Hazwan (Scholar Publishing, 2023)
Parental smoking's impact on children's health risks is concerning, particularly as people spend more time at home due to recent global pandemics. This study examines how parental smoking practices affect children's health risks, including exposure to second-hand smoke, respiratory infections, and asthma. A crosssectional design was employed, collecting data from 207 employees of four higher education institutions in Klang Valley through a structured questionnaire in June and July 2022. Multiple regression was conducted to identify predictors of children's health risks, considering factors such as parental awareness, attitude, and nicotine dependence. According to the study findings, increased parental nicotine dependence, better knowledge about the harmful effects of smoking, and more negative attitudes towards smoking all contribute to a decreased health risk for children exposed to second-hand smoke. However, parental smoking behavior had no significant effect. The public should be made more aware of the elevated health risks that indoor smoking poses for children.